Perspektive razvoja skupnega evropskega azilnega sistema - Kogovšek Šalamon, Neža (Podjetje in delo, 2016)
In the recent years the European Union has been faced with increased numbers of arrivals of people who strive for a better life or flee from persecution, human rights violations or environmental disasters. The responses of the member states to these developments are predominantly based on penalising measures directed against aliens, which was importantly driven by the harmonisation of the EU law in the field of migration and asylum. In the European Union at least 17 member states criminalised unlawful border crossing or unlawful presence and prescribed fines or imprisonment for such crimes. The rest of the member states treat such offences as misdemeanours or criminalise only continuous violation of the law. While human rights are still considered to be a value on the declaratory level, what we can observe in fact is the increasingly intensive merging of crime control and migration control, i.e. criminalisation of migration - crimmigration.
Keywords: azil; človekove pravice; Evropa; Evropska unija; imigranti; migracije; nadzor; zaščita